IMPLEMENTASI TEKNIK MOZAIK DALAM PERKEMBANGAN KEMAMPUAN MOTORIK HALUS DI PAUD AL-ANWAR KONANG GALIS PAMEKASAN - Uswatun Hasanah; Ria Astuti (UIN Mataram, 2020)
This study aims to determine the application of mosaic techniques in the development offine motor skills in PAUD Al-Anwar Konang Galis Pamekasan. Based on this, there are twoproblems that are the main focus in this research, namely: first, how is the application ofmosaic techniques in the development of fine motor skills in PAUD Al-Anwar Konang GalisPamekasan, Second, what are the supporting and inhibiting factors in the application ofmosaic techniques in PAUD Al-Anwar Konang Galis Pamekasan. This research uses aqualitative approach with a descriptive type. Sources of data obtained through interviews,the interview technique that the researcher uses is using semi-structured interviews,because by using this semi-structured interview the researcher is more focused whenasking questions to informants. Observation, the observation used is non-participant,meaning that the researcher does not participate only as an observer. And the last isdocumentation, the data that the researcher wants to find using this method is in theform of photographs, written data. The informants are the principal, the teacher. Whilechecking the validity and carried out through an extension of participation, namely by theresearcher doing a longer study. The results of this study indicate the existence of finemotor development through the activity of mosaic techniques. Thus the authors concludethat the use of mosaic techniques in the development of children's fine motor skillsdevelops optimally because the teacher plans and prepares learning tools and materialsbefore starting a lesson.